Kebijakan Hukum Pidana dalam Penerapan Restorative Justice Pasca Pembaharuan KUHP (Studi di Lapas Medaeng) - Nadyne Erina Saharish; Silfester Enrico Syach Dewa; Davin Arya Putra; Ananda Zydan Ardhi Pratama (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
The reform of Indonesia’s Crimal Code (KUHP) has reshaped national penal policy by strengthening sentencing goal that emphasize restoration, proportionality, and protection of victims and society. In this setting, restorative justice (RJ) becomes increasingly relevant as an approach to mitigate the adverse effects of imprisonment and to promote more humane conflict resolution. This study examines criminal law policy on the application of restorative justice after the KUHP reform, using a case study at Lapas Medaeng (Medaeng Correctional Facility). The analysis focuses on: (1) the normative basis of restorative justice within the new KUHP framework and related regulations; (2) the forms of RJ implementation at the post-adjudication stage (during the execution of punishment) within correctional institutions; and (3) key obstacles and policy needs to ensure effective and accountable practice. Employing an empirical juridical method, the research combines statutory and doctrinal analysis with field data gathered through interviews and observation of correctional programs, mediation initiatives, and social reintegration activities. The findings indicate that opportunities for RJ at Lapas Medaeng exist through rehabilitation-based interventions, facilitated dialogue, community-oriented programs, and efforts to repair social relationships. However, implementation remains constrained by limited operational guidelines, weak inter-agency coordination, insufficient trained facilitators, and the absence of measurable outcome indicators. The study recommends strengthening implementing regulations, developing correctional RJ standard operating procedures, expanding mediator/facilitator training, and establishing robust monitoring and evaluation mechanisms to ensure alignment with sentencing objectives and legal certainty. Keywords: restorative, normative, law, evaluation   Abstrak Pembaharuan KUHP membawa perubahan penting dalam orientasi kebijakan hukum pidana di Indonesia, termasuk penguatan tujuan pemidanaan yang lebih menekankan pemulihan, proporsionalitas, serta perlindungan korban dan masyarakat. Dalam konteks ini, restorative justice (RJ) dipandang sebagai pendekatan yang relevan untuk mengurangi dampak pemenjaraan dan mendorong penyelesaian konflik secara lebih manusiawi. Penelitian ini mengkaji kebijakan hukum pidana dalam penerapan restorative justice pasca pembaharuan KUHP dengan studi di Lapas Medaeng. Fokus kajian meliputi: (1) landasan normatif RJ dalam kerangka KUHP baru dan regulasi terkait; (2) bentuk implementasi RJ pada tahap pasca-adjudikasi/pelaksanaan pidana di lingkungan pemasyarakatan; serta (3) hambatan dan kebutuhan kebijakan agar RJ berjalan efektif dan akuntabel. Penelitian ini menggunakan pendekatan perundang-undangan (statute approach) dan pendekatan konseptual (conceptual approach) untuk menganalisis bagaimana kebijakan pemasyarakatan di Lapas Medaeng seharusnya diimplementasikan berdasarkan paradigma KUHP baru. Hasil kajian menunjukkan bahwa peluang penerapan RJ di Lapas Medaeng terbuka melalui mekanisme pembinaan, fasilitasi dialog, pemulihan relasi sosial, dan program berbasis komunitas, namun masih menghadapi kendala berupa keterbatasan pedoman operasional, koordinasi antar-aparat penegak hukum, ketersediaan fasilitator, serta indikator keberhasilan yang terukur. Penelitian ini merekomendasikan penguatan regulasi turunan, SOP RJ di pemasyarakatan, pelatihan mediator/fasilitator, dan skema monitoring-evaluasi untuk memastikan RJ sejalan dengan tujuan pemidanaan dan kepastian hukum. Kata kunci: restorative, normatif, hukum, evaluasi